Global organ shortage: an analysis of national self‑sufficiency strategies - O. N. Reznik; D. V. Mikhel (Вестник трансплантологии и искусственных органов, 2020)
From the standpoint of socio-humanitarian knowledge, the paper analyzes the problem of global organ shortage. The basic ideas of the international medical community about organ shortage and the main proposals for overcoming it are considered. Special emphasis is placed on the three most revealing national self-sufficiency strategies adopted by donor agencies – American, Spanish and Iranian strategies. The issue of influence of cultural differences and socio-economic inequality on established organ donation practices is discussed using Mexico, Turkey, Pakistan and Bangladesh as examples.